RETRACTED: Li et al. A Kalman Filter-Based Distributed Cyber-Attack Mitigation Strategy for Distributed Generator Units in Meshed DC Microgrids. Energies 2023, 16, 7959 - Wenpei Li; Han Fu; Shun Wu; Bin Yang; Zhixiong Liu (Energies)
The journal retracts the article titled “A Kalman Filter-Based Distributed Cyber-Attack Mitigation Strategy for Distributed Generator Units in Meshed DC Microgrids” [...]